Praxis induction. Definition, relation to epilepsy syndromes, nosological and prognostic significance. A focused review - Yacubian, Elza Márcia Targas [UNIFESP] (2014)
Purpose: There is increasing awareness that reflex epileptic mechanisms provide unique insight into ictogenesis in human epilepsies. Several of the described triggers have in common that they imply complex visuomotor coordination and decision-making; they are today regarded as variations of one principle, i.e. praxis induction (PI). This focused review considers PI from the aspects of history and delineation, clinical and electroencephalographic presentation, syndromatic relations, prevalence, mechanisms of ictogenesis and nosological implications, treatment and prognosis.Methods: We reviewed a series of published articles and case reports on PI in order to clarify clinical and electroencephalographic findings, treatment and outcome.Results: Findings of both induction and inhibition by the same stimuli suggest widening the reflex epilepsy concept into a broader one of epilepsies with exogenous modification of ictogenesis. PI is closely related to juvenile myoclonic epilepsy (JME) where hyperexcitability and hyperconnectivity of the entire network of visuomotor coordination seem to provide the precondition for eliciting reflex myocloni in the musculature active in the precipitating task.Conclusion: the conclusions on ictogenesis derived from PI support the concept of JME as a system disorder of the brain. (C) 2014 British Epilepsy Association. Published by Elsevier B.V. All rights reserved.